A case report on Total Knee Arthroplasty in an young adult with Post-Traumatic Secondary Osteoarthritis with Fixed Flexion Deformity (ROM 0-5) and six months outcome (Pulse, 2025)
This case report presents the management of a young adult with post-traumatic secondary osteoarthritis and a fixed flexion deformity ROM (0-5) of the knee, treated with total knee replacement (TKR). The patient, a 24-year-old male, sustained a complex intra-articular fracture of the knee following a high-energy trauma, which was initially managed by spanning external fixator and dislocation correction along with soft tissue repair. Despite surgical intervention, the patient developed progressive osteoarthritis and a fixed flexion deformity, leading to significant pain, functional impairment, and reduced quality of life. After exhausting conservative measures, including physical therapy and pharmacological management, the decision was made to proceed with TKR. Preoperative planning involved detailed imaging and assessment of bone stock, ligamentous stability, and deformity correction requirements. Intraoperatively, a posterior-stabilized prosthesis was implanted with meticulous soft tissue balancing and correction of the flexion contracture. Postoperatively, the patient underwent an intensive rehabilitation program, achieving full extension and a functional range of motion (ROM 0-130). At the 6-month follow-up, the patient reported marked improvement in pain relief, mobility, and overall function, with no complications. This case highlights the challenges and considerations in performing TKR in young adults with post-traumatic osteoarthritis and fixed flexion deformity, emphasizing the importance of individualized surgical planning and rehabilitation to optimize outcomes in this complex patient population.Pulse Volume 16, Issue 2 2024, P: 31-34